What are the Factors that Cause Domestic Violence? What is the Role and Efforts of the Government in Handling It? - Legawa, Muhammad Raihan Putra (Jurnal Indonesia Sosial Sains, 2024)
This research uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews, participatory observations, and literature studies. Interviews were conducted with victims of domestic violence, family members, and authorities such as the police and social workers. Observation was carried out to observe the condition of families and the surrounding environment who experienced domestic violence cases. Literature studies include a review of laws, regulations, and scientific literature related to human rights and domestic violence. The collected data is then analyzed thematically to understand the pattern of human rights violations in the domestic context and the role of the government and society in handling domestic violence cases. The results of the study show that human rights violations in the form of domestic violence often occur in various forms, including physical, emotional, and economic. Domestic violence victims generally experience fear and dependence on the perpetrator, which prevents them from reporting the case